„Corporation Austria?“ Impact Orientation between Technocracy and Democracy - Brandtner, Christof; Kinschner, Markus; Polzer, Tobias (Momentum Quarterly, 2013)
Public administrations are increasingly controlled via outputs and outcomes rather than by the traditional allocation of financial resources and staff. The Austrian Federal Budget Law Reform of 2013 also reflects this trend. Does the focus on the performance of public administration transform the democratic state into “Austria, Inc.”? According to the critics of management-inspired reforms in the public sector, democracy is threatened to degenerate to a post-democratic spectacle with technocratic forms of governance. In this context, the article discusses the public administration reforms that took place both globally and in Austria, and presents the concept of performance orientation. Next, the “quality of democracy” is operationalized in a six-dimensional analytical framework, based on which we critically discuss the political-democratic implications of outcome orientation. The paper concludes that the outcome orientation breaks with the logic of Weberian bureaucracy to some extent; the expected effects on the legal state and the possibility of decoupling and instrumental rationalization are outlined.